2021
DOI: 10.20885/eksakta.vol2.iss2.art7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metals Concentration in Milk Products by using Atomic Absorption Spectroscopy

Abstract: Milk products are essential food in the human diet because it contains many essential trace minerals such as calcium, magnesium, copper, zinc, sodium, potassium and phosphorous. The utilization of, milk is increasing at a large scale throughout the world. It is essential to maintain the good quality of milk during production and manufacturing because the presence of toxic metals in the milk becomes the cause of health disturbance in human life. Therefore, the present investigation was carried out to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…In leafy green plant samples, the average Cu content was below the recommended permissible limit (73 mg/kg) set by the FAO/WHO. In this study, the average Cu level was lower than the reported value (32.45 mg/kg) in Gamo, Ethiopia [63]. According to the WHO and FAO, the values of Cu and Cr contents in vegetables should not exceed 30 mg/kg.…”
Section: Levels Of Trace Elements In the Studied Samplescontrasting
confidence: 61%
See 1 more Smart Citation
“…In leafy green plant samples, the average Cu content was below the recommended permissible limit (73 mg/kg) set by the FAO/WHO. In this study, the average Cu level was lower than the reported value (32.45 mg/kg) in Gamo, Ethiopia [63]. According to the WHO and FAO, the values of Cu and Cr contents in vegetables should not exceed 30 mg/kg.…”
Section: Levels Of Trace Elements In the Studied Samplescontrasting
confidence: 61%
“…Table 1 demonstrates the levels of trace elements in leaves, shoots, and roots of the four vegetables analyzed in the study area. Vegetables can absorb elements from soil, which can be deposited on parts of vegetables exposed to the air in contaminated environments [63]. The average levels of the trace elements in different organs of leafy green plants (coriander, parsley, arugula, and dill) were successfully compared with the permissible levels set by the FAO/WHO [4], as summarized in Table 1.…”
Section: Levels Of Trace Elements In the Studied Samplesmentioning
confidence: 99%
“…The results varied significantly across plant species and sampling sites, exerting a substantial influence on the plants' absorption capacity as previously discussed. Generally, the results showed that vegetables contained high concentrations of metals [67]. This explains the high concentration of metals found in plant samples from aqueous ecosystems that are continuously exposed to heavy metal pollution.…”
Section: Trace and Heavy Metalsmentioning
confidence: 93%
“…According to reports, zinc compounds were used in the production of paint, dyes, and other ointments, as well as preserved wood. Much zinc exposure has been reported to be harmful and hazardous to health, potentially leading to anaemia, stomach cramps, and cholesterol changes Raikwar et al [10], Abraham and Gholapand [11]. Furthermore, zinc and copper are found in some electrical wires and plumbing pipes, as well as sheet metal used in building construction in some developing countries.…”
Section: Introductionmentioning
confidence: 99%